2013
DOI: 10.1007/s11999-012-2725-5
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Curetting Osteoid Osteoma of the Spine Using Combined Video-assisted Thoracoscopic Surgery and Navigation

Abstract: Background A spinal osteoid osteoma is a rare benign tumor. The usual treatment involves complete curettage including the nidus. In the thoracic spine, conventional open surgical treatment usually carries relatively high surgical risks because of the close anatomic relationship to the spinal cord, nerve roots, and thoracic vessels, and pulmonary complications and postoperative pain. Case Report We report the case of a 16-year-old girl with a symptomatic osteoid osteoma at the T9 level whose lesion was curretta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 36 publications
1
15
0
2
Order By: Relevance
“…However, Gasbarrini et al (15) showed a homogeneous distribution of pathological levels in a study of 81 cases with 28 in the lumbar, 27 in the thoracic and 26 in the cervical regions. The most commonly affected part of the vertebrae is the neural arch in 75% of cases, with 33% involving the lamina, 20% involving the articular facets, and 15% involving the pedicles (16). Pars interarticularis is the most common (73%) site of involvement (7).…”
Section: Incidence Location and Demographic Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Gasbarrini et al (15) showed a homogeneous distribution of pathological levels in a study of 81 cases with 28 in the lumbar, 27 in the thoracic and 26 in the cervical regions. The most commonly affected part of the vertebrae is the neural arch in 75% of cases, with 33% involving the lamina, 20% involving the articular facets, and 15% involving the pedicles (16). Pars interarticularis is the most common (73%) site of involvement (7).…”
Section: Incidence Location and Demographic Characteristicsmentioning
confidence: 99%
“…Surgical options in these patients are open resection or percutaneous techniques such as radiofrequency (RF) thermal ablation and laser coagulation. Experience with percutaneous techniques in extraspinal OOs is quite much; however, in spinal lesions they may be dangerous because of proximity of the lesions to the neural tissues (16). They may be the first choice if the lesion location is appropriate.…”
Section: Treatmentmentioning
confidence: 99%
“…W. Campos и соавт. [13] сообщают об использовании навигационных систем и торакоскопии. Открытое хирургическое лечение на уровне грудного отдела позвоночника имеет от-носительно высокий риск ошибки уровнем.…”
Section: Discussionunclassified
“…Так, по данным W. Campos и соавт. [13], комбинация тора-коскопии и навигационной системы позволила определить точную локализацию и выполнить пол-ное иссечение опухоли через минимально инвазив-ный доступ без ущерба для стабильности позвоноч-ника. В нашей серии перед и во время операции ис-пользовали С-дугу.…”
Section: Discussionunclassified
“…Nagashima et al 22 and Campos et al 4 described the use of stereotactic guidance for curetting the nidus of an osteoid osteoma. The use of navigation made it possible for them to safely curette the nidus through a small hole, thus providing symptomatic relief without the destabilization or limitation of movement that might have resulted from a larger fusion surgery.…”
mentioning
confidence: 99%